Isolated Bilateral Triceps Weakness in Myasthenia Gravis - Betül Özenç; Kübra Işık; Zeki Odabaşı (Acta Neurologica Taiwanica)
Purpose: Myasthenia gravis (MG) is the most common autoimmune disease that affects the neuromuscular junction and can cause weakness in various muscle groups. The most commonly affected muscles are the eye, facial, and neck flexors. Focal or dominant weakness of the triceps muscle is rare. In this case, we aimed to describe a rare form of MG consisting of selective or dominant triceps muscle weakness. Case report: We present a 45-year-old male patient whose initial complaints were diplopia and ptosis. Acetylcholine receptor antibody was positive. After 10 years of well-being following thymectomy, bilateral triceps weakness was added to his ocular symptoms despite regular medication (pyridostigmine and prednisone). Repetitive nerve stimulation (RNS) showed decremental responses in the right triceps muscles. Conclusion: It is important to recognize this type of myasthenia gravis to facilitate diagnosis and appropriate treatment and to avoid unnecessary investigations and treatments.